The effects of a group exercise program on primary school children aged six to ten years diagnosed with Developmental Coordination Disorder (DCD) - Salie, Roshaan (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScPhysio (Interdisciplinary Health Sciences. Physiotherapy))--University of Stellenbosch, 2009.